SITUASI MALARIA DI DESA SANTUUN. KECAMATAN MUARA UYA KABUPATEN TABALONG PROVINSI KALIMANTAN SELATAN TAHUN 2010 - Sunaryo sunaryo (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2012)
Malaria is still becoming public health problem in Tabalong District, South Kalimantan Province. Malaria case in Tabalong during 3 last years experiences improvement, and spread in four Sub District.The study aimed to explains the epidemiology of malaria in Santuun village, Muara Uya Sub District. Santuun village is most endemic area in Muara Uya Subdistrict, malaria control activity which have been done are passive case detection in Health Center / Hospital and entomological survey.Malaria distribution in Santuun village based on time related to rainfall, at high rainfall of malaria cases tend to increase. Most of malaria cases found at male group. Anopheles habit in Santuun is rainwater pond, sleazy pool, cracks, rice field. Anopheles which were found : An. aconitus, An. balabacensis, An. nigerimus, An. barbirostris, An. kochi, An. vagus, An.minimus.